2018
DOI: 10.1097/ajp.0000000000000504
|View full text |Cite
|
Sign up to set email alerts
|

Patients With Knee Osteoarthritis Who Score Highly on the PainDETECT Questionnaire Present With Multimodality Hyperalgesia, Increased Pain, and Impaired Physical Function

Abstract: Objectives:PainDETECT is a self-report questionnaire that can be used to identify features of neuropathic pain. A proportion of patients with knee osteoarthritis (OA) score highly on the PainDETECT questionnaire. This study aimed to determine whether those with a higher “positive neuropathic” score on the PainDETECT questionnaire also had greater pain, hypersensitivity, and reduced function compared with individuals with knee OA with lower PainDETECT scores.Materials and Methods:In total, 130 participants with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
57
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(68 citation statements)
references
References 30 publications
5
57
1
Order By: Relevance
“…Thus, even in the absence of a change in innervation, inflammation can elicit pain in response to normally innocuous stimuli (allodynia) or increase sensitivity to noxious stimuli (hyperalgesia). In many cases bone pain also presents as cutaneous sensitivity at sites surrounding or distant to the injury (referred pain) . This fact has been leveraged in preclinical studies for the relative ease of studying thermal and mechanical sensitivity of the skin near the affected bone as a surrogate for bone pain (reviewed in Nencini and Ivanusic).…”
Section: Bone Painmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, even in the absence of a change in innervation, inflammation can elicit pain in response to normally innocuous stimuli (allodynia) or increase sensitivity to noxious stimuli (hyperalgesia). In many cases bone pain also presents as cutaneous sensitivity at sites surrounding or distant to the injury (referred pain) . This fact has been leveraged in preclinical studies for the relative ease of studying thermal and mechanical sensitivity of the skin near the affected bone as a surrogate for bone pain (reviewed in Nencini and Ivanusic).…”
Section: Bone Painmentioning
confidence: 99%
“…In many cases bone pain also presents as cutaneous sensitivity at sites surrounding or distant to the injury (referred pain). (167)(168)(169)(170) This fact has been leveraged in preclinical studies for the relative ease of studying thermal and mechanical sensitivity of the skin near the affected bone as a surrogate for bone pain (reviewed in Nencini and Ivanusic (171) ). However, preclinical studies that that use cutaneous sensitivity as a surrogate for bone pain may overestimate analgesic efficacy, impacting potential for clinical translational success.…”
Section: Bone Painmentioning
confidence: 99%
“…The predictive value of mechanistic pain profiling in the treatment of osteoarthritic pain Recent reviews have concluded that there is a neuropathic component in a subpopulation of OA patients [6,13]. The PainDetect questionnaire aims to identify a positive, unclear and negative neuropathic pain component in chronic pain patients [20], and studies have identified 5 -30% [32,35,37] of OA patients with a positive neuropathic pain component. Furthermore, OA patients with a positive neuropathic pain component have been found to report higher pain intensities and widespread pressure hyperalgesia compared with an unclear or negative neuropathic pain component [35].…”
Section: Nsaids Plus Paracetamol and Mechanistic Pain Profilingmentioning
confidence: 99%
“…89 A mixture of neuropathic and non-neuropathic pain components were identified not only in chronic nonspecific LBP, 90 but ankylosing spondylitis back pain, 110 and knee and hip OA. 26,36,59,61 However, it is unclear whether a neuropathic pain subgroup exists in other pain conditions. Future studies should investigate whether distinct pain subgroups exist within chronic pain conditions and whether these subgroups present with different M1 changes.…”
Section: Evidence Of Altered M1 Structure Organization and Functionmentioning
confidence: 99%